Transcriptional Analysis of Sepsis-Induced Activation and Damage of the Adrenal Endothelial Microvascular Cells - Chen, Lan-Sun; Singh, Sumeet P.; Müller, Gregor; Bornstein, Stefan R.; Kanczkowski, Waldemar (Frontiers in Endocrinology, 2020)
Bacterial sepsis is a serious threat to the body homeostasis and is often associated with high mortality in non-coronary intensive stations. Sepsis is a very complex and multifactorial but also enigmatic syndrome. In order to survive sepsis, rapid activation of the hypothalamus-pituitary-adrenal gland axis and sympathomedullary system is necessary. However, in many patients with a prolonged stay at the intensive care stations, the function of the adrenal gland was found to be affected. Sepsis-induced adrenal dysregulation has also been observed in mice in the experimental setting, such as LPS-induced systemic inflammation or CLP-induced peritonitis. In mice, sepsis induction resulted in acute inflammation, increased cell death and occurrence of haemorrhages in the adrenal glands. A recent analysis of the adrenal gland transcriptome of mice subjected to sepsis strongly suggested endothelial damage. Whether endothelial dysfunction can cause adrenal gland dysregulation during sepsis is unknown. Therefore, in this study in order to gain a deeper understanding of the potential molecular mechanisms underlying sepsis-induced adrenal vascular damage, we have first characterized and isolated adrenal microvascular endothelial cells and characterized their transcriptomic alteration during systemic inflammation in vivo. The results of our analysis strongly suggest that adrenal endothelium is a key player in pathogen recognition, leukocyte recruitment, and initiation of the inflammation and hypoxia induction. Furthermore, our transcriptomic results demonstrated that sepsis may induce damage to the adrenal gland microvasculature, by activating multiple gene sets regulating inflammation, coagulation, and permeability.